The Effect of Financial Literacy on the Investment Decision - Baihaqqy, Mochammad Rizaldy Insan; Disman, Disman; Nugraha, Nugraha; Sari, Maya; Ikhsan, Sugiyanto (Budapest International Research and Critics University, 2020)
The increase in the economic marketplace and the aging population in Indonesia has resulted in a new understanding of investment. Basically, someone's financial literacy will be in line with investment decisions, because someone already understands the level of risk and the level of return obtained in the future. This study uses a quantitative approach using a survey method involving 400 research samples consisting of Baby Boomers, Generation Xers and Gen-Y / NetGen. The results show that financial literacy has an effect on investment decisions. These results also show a similarity in patterns with research in developed countries and emerging market countries, but show an inconsistency with other studies in Indonesia.